Analysis of Customer Service Strategy for Bank Syariah Indonesia KCP Medan Sukaramai in Improving Excellent Service to Customers - Sitohang, Misbah; Rahma, Tri Inda Fadhila (JESI (Jurnal Ekonomi Syariah Indonesia), 2023)
This study aims to analyze the customer service strategy of Bank Syariah Indonesia KCP Medan Sukaramai in improving excellent service to customers. This study uses a qualitative approach and SWOT data analysis techniques, namely strengths, weaknesses, opportunities, and threats. This research shows that BSI KCP Medan Sukaramai's customer service improving excellent service must pay attention to strategic factors. Strategic factors in terms of strengths (strengths) are using polite language, performing services quickly and precisely, and the ability to remember. Meanwhile, in terms of weaknesses, the network, banking system, and bank image are only intended for the Muslim community. So this strength must be utilized to be able to reach the opportunities that exist, namely that the bank is in an area that is easily accessible by the public because it is passed by public transportation and also Sharia business principles which do not limit customers based on their religion. Weaknesses must be minimized to avoid threats, which the BSI KCP Medan Sukaramai office is close to a private bank, namely Bank Muamalat, which has the potential to be a choice for the community if the service received at BSI KCP Medan Sukaramai is not as expected and people's habits are still frequent. transactions in conventional banks are also a further threat